MOTIVATION OF NURSING STUDENTS TO WORK IN JAPAN: A CASE STUDY OF STIKES NHM BANGKALAN MADURA - Nunuk Endah Srimulyani; Putri Elsy; Hafna Ilmy Muhalla; Christian Yohanes Tarbarita Banjarnahor (Universitas Airlangga, 2023)
This article discusses the interest and motivation of nursing students in Indonesia, specifically in the Madura region, to pursue a career in Japan. Globalization and international mobility have influenced the interest of Madura residents in seeking job opportunities abroad, particularly in the Middle East. However, how do nursing graduates from Madura perceive Japan, a non-Muslim country, as a potential destination for employment. A survey and semi-structured interviews were conducted with 155 nursing students from STIKES Ngudia Husada, including alumni who have recently become nurses and are members of PPNI Bangkalan in Madura. The findings showed that the interest in working in Japan is actually quite high (82.6%), with the main motivating factors being the desire for new experiences (80%) and attractive salaries (49%). Nursing skills required to work in Japan are not a problem because the skill demands for nurses in Indonesia are actually higher. However, language barrier (83.2%), cultural differences, and adaptation issues (both 40.6%) are the main obstacles faced by nursing graduates from Madura in pursuing a career as nurses in Japan. This article proves that although Japan is still considered unfamiliar to Indonesian Migrant Workers in the Madura region, it is considered an attractive destination for nursing students, especially those from STIKES NHM Bangkalan in Madura. However, the challenges of learning the Japanese language, which uses non-alphabetic characters such as Kana and Kanji, as well as the fear of cultural shock due to different work habits and culture, are the biggest obstacles they face. Therefore, Japanese language training, cultural introduction, and understanding of the work ethic of the Japanese society are crucial in enhancing the competitiveness of Indonesian nurses who aspire to pursue a career in Japan.